2021
DOI: 10.1186/s12888-021-03331-x
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent psychopathology and psychological wellbeing: a network analysis approach

Abstract: Background The extent to which psychological wellbeing may play a preventive and therapeutic role in the development and maintenance of adolescent emotional disorders depends, in part, on the nature of the overlap between these two constructs. We estimated network analysis to examine the relationship between adolescent psychopathology (measured by depression and anxiety symptoms) and psychological wellbeing (measured by happiness, optimism, social support, perceived control, and gratitude). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 65 publications
0
22
0
Order By: Relevance
“…Second, self-assessment scales were used in our study, and the results were susceptible to socially desirable responses. Third, although the difference tests of edge weight, centrality and bridge centrality have been widely used in network analysis (93)(94)(95), according to Epskamp et al (32), the methods commonly used in correction for multiple comparison at present are not feasible in network analysis, and new method development is still a topic of future research. Fourth, considering the comorbidity of cognitive impairment, anxiety and depression among the functionally impaired elderly, network analysis including these three may be the direction of future research.…”
Section: Limitationsmentioning
confidence: 99%
“…Second, self-assessment scales were used in our study, and the results were susceptible to socially desirable responses. Third, although the difference tests of edge weight, centrality and bridge centrality have been widely used in network analysis (93)(94)(95), according to Epskamp et al (32), the methods commonly used in correction for multiple comparison at present are not feasible in network analysis, and new method development is still a topic of future research. Fourth, considering the comorbidity of cognitive impairment, anxiety and depression among the functionally impaired elderly, network analysis including these three may be the direction of future research.…”
Section: Limitationsmentioning
confidence: 99%
“…PWB has been defined in terms of specific components of personal growth (including purpose in life, mastery, and self-acceptance) [ 14 ] and by the extent to which psychological needs, namely, autonomy, competence, and connectedness, have been met or thwarted (eg, by mental health symptoms) [ 15 ]. PWB also offers the advantage of being strongly correlated with psychopathology in youth but is also a distinct construct that may provide a basis for the prevention of mental health problems [ 16 ]. In addition, PWB has been identified as having strong transdiagnostic utility in predicting broad psychological outcomes across diverse populations [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides understanding the prevalence and sociodemographic correlates of youth mental health, understanding the association between youth depression and anxiety with psychological wellbeing factors is important because these factors can play a preventive and therapeutic role to circumvent the development of mental health problems (21,22). Because psychological wellbeing indices and youth mental health problems are inversely related, it may be possible to develop interventions that promote psychological wellbeing with the aim of preventing or reducing youth mental health problems (23). In line with this, one study found that the psychological wellbeing indices of social support, gratitude, happiness, and perceived control were negatively associated with both depression and anxiety symptoms (14).…”
Section: Depression and Anxiety Among Kenyan Adolescentsmentioning
confidence: 93%